2020
DOI: 10.1158/2643-3249.bcd-20-0051
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of HIV-Associated Plasmablastic Lymphoma Identifies Pervasive Mutations in the JAK–STAT Pathway

Abstract: Plasmablastic lymphoma (PBL) is an aggressive B-cell non-Hodgkin lymphoma associated with immunodeficiency in the context of human immunodeficiency virus (HIV) infection or iatrogenic immunosuppression. While a rare disease in general, the incidence is dramatically increased in regions of the world with high HIV prevalence. The molecular pathogenesis of this disease is poorly characterized. Here, we defined the genomic features of PBL in a cohort of 110 patients from South Africa (15 by whole-exome sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 57 publications
3
11
2
Order By: Relevance
“…Our analyses in PBL subcohorts further showed that STAT3 mutations predominantly occur in HIV-associated PBLs as these lymphomas harbored significantly more frequently STAT3 mutations compared to other PBL subtypes. In line with our data, a recently published analysis of HIV-associated PBLs reported STAT3 mutations at the same identified mutational hotspots in 42% of investigated cases 9 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our analyses in PBL subcohorts further showed that STAT3 mutations predominantly occur in HIV-associated PBLs as these lymphomas harbored significantly more frequently STAT3 mutations compared to other PBL subtypes. In line with our data, a recently published analysis of HIV-associated PBLs reported STAT3 mutations at the same identified mutational hotspots in 42% of investigated cases 9 .…”
Section: Discussionsupporting
confidence: 92%
“…Roughly 50% of PBL cases harbor MYC translocations that usually rearrange MYC to the heavy chain immunoglobulin locus suggesting an essential role of MYC in the biology of PBL. Recently, a small study using targeted sequencing identified PRDM1 , STAT3 , BRAF , and EP300 mutations in primary PBL samples 8 , whereas another analysis focused on HIV-associated PBL that revealed recurrent mutations of the JAK-STAT pathway 9 . However, due to the small sample size respectively the focus on HIV positive PBL, the landscape of genetic aberrations in PBL, and the exact functional role of these abnormalities in the molecular pathogenesis of PBL remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we saw mutations associated with SOCS1 (two cases in EBV-positive HIV DLBCL), which is a negative regulator for STAT3 23 and which is also found to be mutated in cases of HIV-associated plasmablastic lymphoma. 14 These findings raise the possibility that EBV-positive plasmablastic lymphoma and EBVpositive HIV-DLBCL may share some common genetic alterations in addition to EBV association, a tendency toward post-germinal centre/terminally differentiated B-cell origin, development in patients with more profound immunodeficiency with lower CD4 counts, and worse OS.…”
Section: Discussionmentioning
confidence: 93%
“…All but one of the cases with a STAT3 abnormality was within the SH2 domain. Since the RAS-MAPK pathway has been implicated in other HIV-associated lymphomas, 14,15 we investigated genes related to this pathway and found three EBV-positive HIVassociated DLBCL with NRAS mutations and none in the EBV-negative HIV-DLBCL. One case had a mutation with BRAF but the EBV status of this HIV-DLBCL is unknown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation